Meninjau Upah Buruh Tani dalam Perspektif Ekonomi Islam: Studi Kualitatif tentang Keadilan dan Kesejahteraan - Muhammad Syahrul Hidayat; Agus Eko Sujianto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to analyze farm labor wages from an Islamic economic perspective with a focus on justice and welfare. Through a qualitative approach, this study explores the experiences and perceptions of farm workers regarding their wages and their impact on justice and welfare. The principles of distributive justice, proportional justice, and the elimination of usury in Islamic economics are the theoretical basis used to analyze the agricultural labor wage system. Data and information were obtained through in-depth interviews with farm workers in certain areas. The content analysis results are used to identify patterns related to fair wages and factors that affect the welfare of farm workers. This research shows that agricultural workers often face low and inadequate wages, which negatively impacts their welfare and that of their families. From an Islamic economic perspective, fair wages for agricultural laborers and providing welfare are important for achieving social justice and economic sustainability. This research provides insight into how the principles of Islamic economics can be applied in the agricultural labor wage system to achieve justice and improve welfare. The results of this research are expected to contribute to the development of policies that are in favor of justice and the welfare of farm workers in the context of Islamic economics.